Challenges in teachers’ performance appraisal: A qualitative study on structural flaws and systemic inequities - Mukhtar, Nor Azuanee; Mohd Noor, Mohd Asri; Abdul Majid, Nur Arifah; Zailan, Nur Azilla; Zailan, Nurul Rizuana (International Business Education Journal, 2025)
This research article is a qualitative study on the structural flaws and systemic inequities in teacher performance appraisal practices in Malaysian primary schools. Adapting the in-depth interviews with three experienced school teachers from three different schools in Selangor, the data were analysed using Braun and Clarke’s thematic analysis framework. This research explores how appraisal processes are experienced on the ground, particularly regarding the matter of fairness and recognition. Four main themes emerged: administrative bias, lack of transparency, diminished teachers’ morale or motivation, and the urgent need for systemic reform. Teachers described the appraisal systems as inconsistent, vague, and often shaped by favouritism rather than objectivity in the performance measured. Theoretically, the study advances Adams’ Equity Theory by demonstrating how sustained imbalances between teachers’ effort and recognition, produced by both distributive and procedural injustice, are contributing to demotivation, distrust in leadership, and disengagement from professional growth. From a practical view, the findings accentuate the need for policy-oriented transformation, which includes the implementation of systemic rubrics, transparent evaluation procedures, and structured mentoring mechanisms. These strategies are demanding in aiming to restore appraisal credibility, strengthen teacher motivation, and enhance institutional trust. This study utilised Adams’ Equity Theory in teachers’ performance appraisals, and it demonstrates that inequitable practices occurred in schools and hopes to offer evidence-based insights to educational policymakers and school leaders to seek and redesign the appraisal practices by promoting equity, accountability, and sustainable teacher development.